2005
DOI: 10.2320/matertrans.46.2830
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relaxation in Supercooled Liquids

Abstract: Relaxation behavior of structural change at the atomic cluster level in supercooled liquids during isothermal annealing processes is investigated for a model alloy system by using molecular dynamics simulations. The simulation results show that the number density of icosahedral clusters increases with the annealing time. Moreover, the number density of icosahedral clusters, the structural relaxation time, and the atomic diffusivity strongly correlate with the packing density of the supercooled liquids for many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…On the other hand, an off-eutectic composition as a solvent-rich composition is effective in enhancing the stability of glass structures through the formation of icosahedral-like clusters. 24,25) If the thermal stability of a glass structure depends on the quantity of icosahedral-like cluster formation, an optimized alloy composition should be formed by achieving a balance between the glass-firming ability and the stabilization of the glass structure. Figure 9 shows the relationship between the CUE values and the density of as-cast and annealed Zr 59 Cu 31 Al 10 BGAs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an off-eutectic composition as a solvent-rich composition is effective in enhancing the stability of glass structures through the formation of icosahedral-like clusters. 24,25) If the thermal stability of a glass structure depends on the quantity of icosahedral-like cluster formation, an optimized alloy composition should be formed by achieving a balance between the glass-firming ability and the stabilization of the glass structure. Figure 9 shows the relationship between the CUE values and the density of as-cast and annealed Zr 59 Cu 31 Al 10 BGAs.…”
Section: Discussionmentioning
confidence: 99%
“…The glass-forming range by rapid quenching from liquid phases in this model system has been investigated in the previous studies [33][34][35] and the results are shown in Figure 8. The color of the glass-forming region indicates the cooling rate, where a darker region corresponds to a lower cooling rate.…”
Section: Atomic Size Effect On Glass-forming Ranges Of Model Binary Smentioning
confidence: 99%
“…Thus, the volume of a given atom is the volume of the polyhedron. Using this analytical technique as an analysis tool of atomic structure, a number of researchers have investigated the internal structure of metallic glasses [2,3,6].…”
Section: Introductionmentioning
confidence: 99%